(untitled) (Bangladesh Journal of Orthodontics and Dentofacial Orthopedics, 2013)
This article describes our treatment of Class II, division 2 adult patients requiring premolar extractions. Division 2 cases are often characterized by severe deep bites, lingually inclined upper central and lower incisors, and labially flared maxillary lateral incisors. This patients also tend to exhibit problems with the upper and lower occlusal planes, such as deep curves of Spee, High lip line, marked labiomental depression. Because of the deep bite and supra eruption of the maxillary incisors, the gingival margins of the maxillary anterior teeth are malaligned, and the lingually inclined mandibular incisors have excessively high gingival margins ( Fig. 1 ). The treatment protocol for this patients includes extraction of premolars both upper and lower in right side to relieve crowding, with simultaneous correction of the deep bite by intrusion of the upper and/or lower incisors. Intrusion mechanics are performed with a bite opening bend on a preformed nickel titanium arch wire. Space closure is accomplished with power chain and guard behind the extracted site in anchor plate. Extraction of upper premolar and lower 1st molar (tooth no 36) in left side was done earlier. A 21 years old women with Cl-II Div-II malocclusion type B came to Dental Centre, Dhaka, with chief complaint of an unhappy smile. Retroclined 4 Incisors, Deep bite, Crowding, deficient lower facial height, Gummy smile and a moderately convex hard- and soft-tissue profile because of a retrusive mandible with over jet of 1.5mm and over bite of 6 mm was observed. The mechanics plan should be individualized based on the specific treatment goals. Camouflage Treatment was done with the help of an anchor plate incorporated anterior incline plane. Intrusion mechanics are performed with preformed nickel titanium Connecticut Intrusion Arch (CIA) and anchor plate incorporated bite plane. Treatment was successfully completed with extractions of both pre-molars in right side and left lower 1st molar (Tooth no 36) and upper 1st premolar(Tooth no 24) already extracted ( Fig. 2 A) before starting of orthodontic treatment. Treatment of 20 months which improves incisor inclination, Deep bite correction; eliminate crowding, normal smile line and improvement of gummy smile. With the above mentioned protocol normal inclination of both upper-lower incisor, normal over jet and over bite were also achieved. DOI: http://dx.doi.org/10.3329/bjodfo.v1i2.15987 Ban J Orthod & Dentofac Orthop, April 2011; Vol-1, No.2, 18-24